2023
DOI: 10.1038/s41420-023-01481-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of liensinine in sensitivity of activated macrophages to ferroptosis and in acute liver injury

Jing Li,
Qi Huang,
Minling Lv
et al.

Abstract: Acute liver injury (ALI) is an acute inflammatory liver disease with a high mortality rate. Alternatively, activated macrophages (AAMs) have been linked to the inflammation and recovery of ALI. However, the mechanism underlying AAM death in ALI has not been studied sufficiently. We used liensinine (Lie) as a drug of choice after screening a library of small-molecule monomers with 1488 compounds from traditional Chinese remedies. In ALI, we evaluated the potential therapeutic effects and underlying mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…TCM and its derivatives have shown great therapeutic potential for ALI. Although the mechanisms are not exactly the same, ginsenoside Rd [100], bicyclol [101], gandankang [102], sulforaphane [83], genipin [53], baicalein [103], liensinine [104],…”
Section: Acute Liver Injury (Ali)mentioning
confidence: 99%
See 1 more Smart Citation
“…TCM and its derivatives have shown great therapeutic potential for ALI. Although the mechanisms are not exactly the same, ginsenoside Rd [100], bicyclol [101], gandankang [102], sulforaphane [83], genipin [53], baicalein [103], liensinine [104],…”
Section: Acute Liver Injury (Ali)mentioning
confidence: 99%
“…TCM and its derivatives have shown great therapeutic potential for ALI. Although the mechanisms are not exactly the same, ginsenoside Rd [ 100 ], bicyclol [ 101 ], gandankang [ 102 ], sulforaphane [ 83 ], genipin [ 53 ], baicalein [ 103 ], liensinine [ 104 ], artemisitene [ 105 ], glycyrrhizin [ 106 ], niujiaodihuang detoxify decoction [ 107 ], and low-polarity fraction from Ficus pandurata Hance [ 108 ] have all been shown to alleviate CCl-4 or LPS/ D-gal-induced ALI via preventing ferroptosis. NRF2, GPX4, and lipid metabolism-related enzymes such as ALOX12/15 and ACSL4 are the major targets of these TCMs.…”
Section: Nac Treat Liver Disease By Targeting Ferroptosismentioning
confidence: 99%
“…The relationship between autophagy and ferroptosis is well-established. mTOR, an autophagy inhibitor, also inhibits ferroptosis by regulating GPX4 synthesis [ 56 ], while liensinine protects against acute lung injury by enhancing M2 macrophage resistance to ferroptosis through autophagy regulation [ 57 ]. Interestingly, both pyroptosis and autophagy promote ferroptosis, but not each other, exhibiting an antagonistic relationship.…”
Section: Interactions Between Different Types Of Pcd In Macrophagesmentioning
confidence: 99%
“…M2-type macrophages, known for their role in inflammation and recovery from ALI [ 57 ], may be susceptible to ferroptosis, potentially affecting survival and liver function in LPS/GalN-induced ALI. Investigating the potential therapeutic effects and mechanisms of action of liensinine in ALI, researchers observed an increased survival rate and reduced inflammatory factor production in LPS/GalN-treated mice treated with liensinine.…”
Section: Effect Of Macrophage Pcd On Liver Diseasementioning
confidence: 99%
“… 435 Various hepatotoxic factors, including lipid deposition, viruses, and drugs, can induce ALI. Emerging studies have suggested that ferroptosis plays a role in the genesis of ALI 436 – 444 and have revealed the roles of epigenetic regulation of ferroptosis by ubiquitination in ALI 410 415 (Table 10 ). Mesenchymal stem cells (MSCs) and MSC-derived exosomes (MSC-Exos) alleviate injury through ferroptosis inhibition by decreasing the mRNA levels of Ptgs2 and LOXs while increasing the protein level of SLC7A11 in CCl 4 -induced ALI.…”
Section: Epigenetic and Posttranslational Modifications Regulating Fe...mentioning
confidence: 99%